Research progress on the association of psoriasis with hyperuricemia - Yang LI; Junjie LIN; Xiuqiu LIN; Min OU; Yunling YAN; Xiaohua WANG (Pifu-xingbing zhenliaoxue zazhi, 2022)
It is generally accepted that psoriasis is associated with hyperuricemia. But the exact underlying mechanisms are unclear. Studies demonstrate that the genetic factor is one of the common causes and that the involvement of monosodium urate crystals (MSU) in the inflammatory response is linked to the pathogenesis of psoriasis. Moreover, the activities of purine-related enzymes can promote the development of hyperuricemia in psoriatic patients. Therapies that reduce uric acid can effectively attenuate the risk of cardiovascular and metabolic disorders and prevent the progression and exacerbation of psoriasis in psoriatic patients with hyperuricemia. Understanding the impact of hyperuricemia on psoriasis will benefit the treatment of psoriasis. This review expounds the association of hyperuricemia with psoriasis in the aspects of pathophysiology and the treatment.